The Role of Stakeholders in the Sustainability of PT Pertamina Patra Niaga Fuel Terminal Rewulu's CSR Program (Study on Independent Women's Group "Berlian Progo") - Rifaldi Maulyansyah; Duta Wahyu Wijaya; Hasna Fillari Sofia; Agil Najjah Syifani (ENVIBILITY: Journal of Environmental and Sustainability Studies, 2023)
Limited employment opportunities can cause social problems and impact on economic growth, especially in developing countries like Indonesia. In an effort to overcome this problem, the role of stakeholders such as the government social institutions, the private sector, and the community itself is needed. The purpose of this study was to look at the role of stakeholders in the sustainability of PT Pertamina Patra Niaga Fuel Terminal Rewulu’s CSR Program through the Berlian Progo Mandiri Women’s Group. Therefore, what is the role of stakeholder groups in the sustainability of PT Pertamina Patra Niaga Fuel Terminal Rewulu’s CSR Program? This research method is descriptive qualitative, with data collection techniques through interviews, documentation, and observation. The results of this study indicate that in the empowerment process, so that the programs being implemented can be sustainable and continue to develop, the role of local stakeholder is needed. In this study, it was found that the role of stakeholders in PT Pertamina Patra Niaga Fuel Terminal Rewulu's CSR program (the Berlian Progo Mandiri Women's Group study) was in accordance with the analysis of the Pentahelix model used, namely academics, business/private sector, community/society, government, and media.